2019
DOI: 10.5539/ijms.v11n1p134
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perceived Social Media Marketing Activities: An Empirical Study in Saudi Context

Abstract: Purpose -The purpose is to investigate the impact of social media marketing activities in the context of Saudi consumers of social media. A research model is developed in this study to examine the relationships.Design/methodology/approach -This research is quantitative and uses the probability sampling technique, simple random sampling. Data is collected through a questionnaire in a survey of 241 Saudi social media users. Structural equation modeling (SEM) with PLS 3 was used with SPSS 22.0 for statistical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
2
16
0
2
Order By: Relevance
“…A relationship has been found between the social media marketing activities and E-WOM. The impact of brand loyalty on E-WOM and impact of E-WOM has been found significantly positive with purchase intention (KHAN, 2019).…”
Section: Literature Reviewmentioning
confidence: 89%
“…A relationship has been found between the social media marketing activities and E-WOM. The impact of brand loyalty on E-WOM and impact of E-WOM has been found significantly positive with purchase intention (KHAN, 2019).…”
Section: Literature Reviewmentioning
confidence: 89%
“…This study is also in line with a similar study conducted by Ali, et al (2016) who found that social media marketing influences consumer perceptions. Likewise, in research conducted by Ismail (2016) and Khan (2019) who found that social media marketing has an influence on value consciousness.…”
Section: The Effect Of Social Media Marketing On Perceived Valuementioning
confidence: 95%
“…by Ismail (2017) and Khan (2019) stated that social media marketing has an influence on value consciousness. Based on the statement above, the hypothesis can be formulated as follows:  H5: Social media marketing has a positive effect on perceived value.…”
Section: Social Media Marketing and Perceived Valuementioning
confidence: 99%
“…Value consciousness, Khan (2019)defines value consciousness as the behavior of customers who actively tend to shop on social media platforms at the lowest price. The customers shop by prioritizing saving money and looking for the right item according to the customers' needs and comparing with other brands.…”
Section: Introductionmentioning
confidence: 99%
“…Tatar & Eren-Erdoğmuş ( 2016) also reveal that social media marketing activities in the hospitality business affect customer brand awareness, purchase intentions, and brand loyalty. Likewise, Khan (2019)states that perceived social media marketing activities have an effect on brand loyalty, making social media activities higher, and it will lead to brand loyalty.…”
Section: Introductionmentioning
confidence: 99%